Flexural properties of mmt reinforced unsaturated polyester/epoxidized palm oil biobased resin - Mustapha, Siti Noor Hidayah (2015)
New bio-based thermoset resin was synthesized by blending unsaturated polyester (UPE) and epoxidized palm oil (EPO) together with layered silicate nanoclay (MMT). The biobased polyester resin was processed by 1.5phr benzoyl peroxide initiator. In this study, EPO was added at 10 wt%, while the layered silicate added at 1, 1.5 and 2 phr. The MMT nanoclay was sonicated with acetone for two hours and followed by adding UPE. The MMT, acetone and UPE solution were then dried on a hot plate for 24 hours and followed by vacuum oven for 30 minutes. Then, the EPO and styrene were added to the solution. The sample was cured in an oven at 100 °C (2 hours) and followed by post curing at 160 °C (2 hours). Flexural properties of the UPE/EPO bioresin were experimentally characterized. It was found that, addition of nanoclay improved the flexural modulus of UPE resin. However, the dropped modulus of the resulted bioresin was not recovered by the addition of up to 2 phr MMT. Addition of low percentage MMT nanoclay, which was 1 phr gave a very significant improvements on the dropped flexural strength of UPE/EPO bioresin. The distribution of the MMT nanoclay in the UPE/EPO bioresin sytem was further analysed by X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) images.